Temperature characteristics of surface acoustic wave resonators prepared on (0°, 90°, ψ) CTGS cuts. (15th June 2022) - Yang, Yuntao; Peng, Bin; Yue, Huhu; Huang, Fei; He, Peng; He, Zhengxi; Zhu, Jialiang; Zhang, Wanli
Highlights: The temperature-dependent characteristics of the SAW resonators on (0°, 90°, psi) Ca3 TaGa3 Si2 O14 (CTGS) cuts were investigated systematically . The psi is from −90° to 90° with interval of 15°. The second order temperature coefficients of frequency (TCF2 ) has small fluctuations as the psi is smaller than 30°. From −100 °C to 400 °C, the relative resonance frequency shift changes linearly with the temperature. In the wide range of −100 °C to 1100 °C, the frequency-temperature response of SAW sensor shows obvious quadratic function relationship . Abstract: Surface acoustic wave (SAW) resonators were prepared on (0°, 90°, ψ) Ca3 TaGa3 Si2 O14 (CTGS) cuts. The temperature-dependent characteristics of the SAW resonators were investigated systematically in this work. When ψ is around 40°, the TCF1 (first-order temperature coefficient of frequency) is close to zero and turnover temperature is around room temperature, which can be used for temperature compensation. When ψ changes from 0° to 30°, the turnover temperature is below absolute zero, indicating that the resonance frequency changes monotonically in rather wide temperature range, such as from cryogenic to ultrahigh temperatures. When ψ is 0°, the TCF1 is −32 ppm/°C, contributing to a good temperature sensor with wide operating temperature range. The results in this work can provide valuable references for the design and preparation of SAW devices on CTGS.